Hygienic Instructional Multimedia Improvement for Viable Hi-Tech Enactment in Covid-19 Pandemic Era in Primary Schools - AWUJA, Samuel Ademu (Ilorin Journal of Education, 2023)
The paper focuses on hygienic instructional multimedia improvement for viable hi-tech enactment in primary schools as the nexus for school hygienic status. It compacts with a planned multiple hygienic programs that translate essential healthy living environment such as avoidance of poor sanitation capable of spreading cholera, diarrhea, typhoid fever and biochemical oxygen demand (BOD). BOD is a measure of oxygen pollution. As a matter of necessity, adequate clean water supply to aid primary hygienic instructional multimedia enhancement within school communities in area of drinking, cooking, washing and supporting various small scale agricultural activities or gardens. Furthermore, provision of different types of latrine like bucket latrine, pit latrine, septic tank systems and incineration latrine are basic facts about hygiene, sanitation and sanitary systems in school environments. Enactment of the primary hi-tech hygienic multimedia improvement instruction is targeted at transmitting better hygienic curriculum awareness, skills and practices to primary school pupils as the nexus in Nigerian educational system. Lack of hygienic multimedia instructors, learners’ poor home training, disinterest, inadequate hi-tech instructional multimedia facilities plus inadequate funding by the government kick against its enactment. Therefore, the government should collaborate with hygienic multimedia instructors in primary schools and curriculum planners/ developers to constantly fund hygienic instructional improvement for viable hi-tech enactment in primary schools via conferences/ seminars, webinars and training of hygienic educators among other things to attain the set goals in the policy document.